Incidence of Dolichotetranychus floridanus (Acari: Tenuipalidae) on Arecanut plantation - Prabheena, P. ,; Ramani, N. , (International Journal of Agricultural Technology, 2015)
Areca catechu Linn. is one of the most important plantation crops cultivated in Northern districts of Kerala. The kernel obtained from the areca-nut used in many countries for chewing, in tender, ripe or processed form. Reports indicated that several arthropod pests associated with arecanut palm and cause major economic loss. Recently phytophagous mites have been recognized as serious pests of Areca palm especially young palms, assuming high populations after the onset of hot weather. In the present study, attention has been focused on the incidence and damage symptoms of a tenuipalpid mite of the genus Dolichotetranychus floridanus infesting the Areca palms of various localities of Malappuram, Thrissur and Kozhikode districts of Kerala. Various life stages of this mite were found inhabiting inside the inner whorls of the perianth of tender nuts, feeding on the epicarp and causing considerable damage to the developing fruits. The initial symptoms of attack included the development of brown patch at the base of the young nut at the level of the perianth. Later these patches were enlarged and the epidermis developed cracks and occasionally deep fissures. In severe cases, nut got shriveled, resulting in fall. Infested plantations revealed the presence of varying numbers of such fallen nuts, which on observation under the microscope revealed the presence of eggs, nymphs and adult stages of the mite.